INCREaSE Proceedings of the 1st International Congress on Engineering and Sustainability in the XXI Century - INCREaSE 2017 (Springer International Publishing, 2018)
This book presents the proceedings of the INternational CongRess on Engineering and Sustainability in the XXI cEntury - INCREaSE 2017, which was held in Faro, Portugal, from October 11 to 13, 2017. The book promotes a multidisciplinary approach to sustainable development, exploring a number of transversal challenges. It discusses natural and anthropogenic risks; tourism and sustainability; healthy food; water and society; sustainable mobility; renewable energy; and energy efficiency, offering perspectives from civil, electronics, mechanical and food engineering.